Knowledge, attitudes, and practices among oncologists regarding the implementation of DRGs payment system: a cross-sectional study in Beijing - Xu, Changdan; Zhang, Hong; Yin, Shiquan (Frontiers in Public Health, 2024)
BackgroundThe KAP survey evaluates health-related knowledge, attitudes, and practices through a structured questionnaire. By collecting qualitative and quantitative data, it measures the current situation, tests hypotheses, and provides insights for enhancing health behaviors and education. In 2019, the National Health Security Administration (NHSA) initiated DRG payment reforms. This study aims to improve the quality of health insurance and policy implementation by assessing physicians' knowledge, attitudes, and practices regarding the DRG system.MethodThis study was a cross-sectional study designed with a questionnaire through simple random sampling method, and respondents were the doctors in the clinical departments of the sampled hospitals. The questionnaire included basic information, knowledge about DRGs, attitude toward DRGs and practice of implementation. Data were analyzed using descriptive statistical analysis, correlation, path analysis and generalized linear model.ResultA total of 210 questionnaires were included. The majority of respondents aware that their healthcare organizations had already begun to implement the policy. With a mean score of 7.67 for knowledge, respondents basically had a good level of knowledge of DRGs. The mean attitude score of the respondents was 30.20, which was lower than the “positive attitude” criterion, and their main concerns were about matters other than treatment. Knowledge scores were significantly correlated with attitude scores (P < 0.001), whereas attitude scores were not associated with practice scores. Path analysis and generalized linear modeling indicate that knowledge effectively influences attitudes, whereas attitudes do not have an apparent impact on practice.ConclusionOncologists' understanding of DRGs needs to be improved, and their knowledge and attitudes have not yet translated into demonstrable positive practice behaviors. This gap underscores the need for knowledge training and effective incentives.